Fekete-Szegö Problems for Quasi-Subordination Classes - Maisarah Haji Mohd; Maslina Darus (Abstract and Applied Analysis)
An analytic function f is quasi-subordinate to an analytic function g, in the open unit disk if there exist analytic functions φ and w, with |φ(z)|≤1, w(0)=0 and |w(z)|<1 such that f(z)=φ(z)g(w(z)). Certain subclasses of analytic univalent functions associated with quasi-subordination are defined and the bounds for the Fekete-Szegö coefficient functional |a3-μa22| for functions belonging to these subclasses are derived.